Logophoricity-and-Discourse Syntax in Indonesian - I Nyoman Udayana,; Ni Luh Ketut Mas Indrawati, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Indonesian lacks dedicated logophoric pronouns. Instead, logophoric references are encoded through the use of reflexive pronouns within the discourse context. This study aims to elucidate the relationship between reflexive anaphors and logophoricity in Indonesian. Specifically, it seeks to demonstrate that a particular form, namely the complex reflexive formed by combining diri with possessive pronouns, is exclusively associated with logophoricity. The data for this study was extracted from naturally occurring expressions found in the Leipzig corpora. Analysis was conducted using discourse syntax, which examines the interplay between syntax and the surrounding textual environment, to observe the resulting phenomena. The findings indicate that logophors in Indonesian differ significantly from reflexive anaphors in four key aspects. Firstly, logophoric pronouns, unlike reflexive pronouns, can be bound at a long distance. Nevertheless, they still adhere to the principles of binding theory regarding their antecedents. Secondly, logophoric pronouns may not necessarily agree in phi features with their antecedents. Thirdly, the logophoric anaphor can occupy various grammatical functions, including both object and subject positions. Lastly, unlike reflexivization, logophoric constructions in Indonesian are subject to passivization.